DEPRESSION AND QUALITY OF LIFE IN PATIENTS WITH PEMPHIGUS: A CROSS-SECTIONAL STUDY - MAGHADE, MEGHA; SAOJI, ANAND; SOMANI, ABHISHEK; FAYE, ABHIJEET (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of the study is (1) to analyze the prevalence and severity of depression in cases of pemphigus and (2) to study the association of demographic factors with the presence of depression in cases with pemphigus. Methods: A cross-sectional single-interview study was carried out on 100 consecutively selected patients with pemphigus attending the dermatology out-patient department in a tertiary care hospital. The assessment was done with semi-structured pro forma, Beck depression inventory (BDI), and quality of life (QoL) measure – Skindex-16. The Statistical Package for the Social Sciences 24.0 was used for statistical analysis and p<0.05 was taken as statistically significant. Results: Out of 100 cases, there were 60 (60%) males and 40 (40%) were females with M: F ratio of 1:0.66. The mean age of male and female patients was found to be comparable with no statistically significant difference (p=0.6061). The majority were married, employed, and from rural backgrounds. 22% satisfied the Diagnostic and Statistical Manual for Mental Disorders 5th edition criteria for major depressive disorder. Assessment using BDI in these patients for severity of depression showed mild depression in 12%, moderate depression in 7%, and severe depression in 3%. Patients having a longer duration of illness and a history of frequent hospitalization were found to have significantly high scores on the subscale for depressive symptoms. QoL assessment using the Skindex-16 scale among these patients showed that they experienced more severe emotional and symptomatic effects due to skin disease compared to functional effects, especially during relapse. Those who had poor QoL showed significantly high scores on the subscale for depressive symptoms. Conclusion: More than 20% of patients of pemphigus had diagnosable depression with significant effects on QoL. Therefore, regular screening for depression is important in pemphigus patients as it will help in planning early intervention.